Worksheet for Ethnoscience-Based Practicum Learning Supported by Simulation Tools: Design and Validation Results - Verawati, Ni Nyoman Sri Putu; Rokhmat, Joni; Harjono, Ahmad; Makhrus, Muh (Universitas Pendidikan Mandalika, 2025)
This study aims to develop and validate an ethnoscience-based practicum worksheet supported by virtual simulation tools to enhance culturally contextualized science learning. The integration of ethnoscience into science education responds to the need for pedagogical models that connect scientific concepts with students' local cultural knowledge, particularly in educational institution facing limited access to laboratory resources. Utilizing a research and development approach, the study was conducted through three main phases: preliminary investigation, design and construction, and evaluation and revision. The worksheet was structured to include scientific inquiry stages such as observation, hypothesis formulation, virtual experimentation, data analysis, and reflection. Expert validation was conducted using the Delphi method involving six experts in science education, ethnoscience, and educational technology. A Likert scale (1–5) instrument was used to assess content and construct validity, yielding average scores of 4.738 and 4.792 respectively, with a 95.83% agreement rate, indicating high validity and reliability. Suggestions from validators led to improvements in instructional clarity and contextual integration. The results confirm that the developed worksheet is pedagogically sound, technically feasible, and culturally relevant, aligning with 21st-century learning objectives that emphasize critical thinking, inclusivity, and digital literacy. This research offers a practical model for integrating ethnoscientific content with educational technology and contributes to the ongoing development of innovative, inclusive, and adaptive science education practices in Indonesia. Future applications may extend to diverse local contexts, supporting a more holistic and culturally grounded approach to science instruction.